An upconversion nanosensor for rapid and sensitive detection of tetracycline in food based on magnetic-field-assisted separation. (30th March 2022) - Zhang, Yunlian; Mehedi Hassan, Md; Rong, Yawen; Liu, Rui; Li, Huanhuan; Ouyang, Qin; Chen, Quansheng
Highlights: Core-shell europium doped upconversion nanoparticles were synthesized successfully. Eu 3+ exposed UCNPs and aptamer were applied as tetracycline (TCY) recognition probes. Magnetic separation and electrostatic adsorption-based TCY sensing method has developed. A fluorescence method for TCY achieved a detection limit of 0.17 ng·mL −1 . Abstract: Tetracycline, a broad-spectrum antibiotic, has been widely used in disease treatment and other fields. However, due to the unreasonable use, its residue remains in food which eventually harms human health. Here described an upconversion nanosensor for tetracycline detection based on magnetic separation and electrostatic adsorption. To identify tetracycline, tetracycline aptamer, and europium ions (Eu 3+ ) were introduced in the system. According to the electrostatic adsorption principle, Eu 3+ exposed core–shell UCNPs were bound to negative complex of magnetic nanoparticles (MNPs) and aptamer. In the presence of tetracycline, UCNPs separated with MNPs-aptamer and remained in the supernatant by an external magnetic field. Under optimal conditions, the linear detection range of tetracycline was 0.5–1000 ng·mL −1, and the detection limit was 0.17 ng·mL −1 . It has been successfully applied to detect tetracycline in food samples. The constructed method provided broad prospects for tetracycline detection with the merits of simple operation, high sensitivity, excellent repeatability, and selectivity.